Therapists' Perceptions of Individual Patient Characteristics that May Be Hindering to Group CBT for Anxiety and Depression. Issue 4 (1st October 2020) - Bryde Christensen, A.; Svart, N.; Bokelund, H.; Reinholt, N.; Eskildsen, A.; Poulsen, S.; Hvenegaard, M.; Simonsen, E.; Arnfred, S.
Abstract : Objective : Individual patient characteristics are important in trying to understand why people respond differently to group CBT. Only a few studies have explored therapists' perceptions of within-patient attributes that may be hindering in group CBT in a mental health setting. Method : We explored the perception of individual patient characteristics and related obstacles in 12 psychotherapists in Danish Mental Health Services through semi-structured interviews. The interviews were analyzed using a descriptive qualitative framework. Results : The results revealed four distinct themes that the therapists pointed to as important for the outcome of a 14-week group CBT intervention for social phobia, panic disorder, agoraphobia and major depressive disorder. The four themes were Complexity & severity, External circumstances, Attitudes & coping and Cognitive ability & reflection level. The therapists explained how they perceived higher complexity and severity in the patients as an obstacle, they highlighted that a calm and stable outside environment aided therapeutic change, whilst stressors were hindering. They perceived active coping mechanisms, positive attitudes and high readiness to change as positive factors, whilst dependent and hostile coping mechanisms and negative attitudes were seen as obstacles. Finally, the therapists pointed to cognitive abilities and reflection level, explaining how it could be difficult to obtain good outcomes for patients who's cognitive abilities were debilitated due to psychopathological factors or for patients with a generally low reflection level. Conclusions : The results indicated that the therapists experience group CBT as an intervention that requires certain prerequisites of the patients, and that the four themes should be considered when deciding on treatment options for any given patient. The clinical utility and theoretical implications of the results are discussed.